Effects of a computerised protocol management system on ordering of clinical tests. - Nightingale, P G (1994)
OBJECTIVE--To assess the effects of a computerised protocol management system on the number, cost, and appropriateness of laboratory investigations requested. DESIGN--A before and after intervention. SETTING--A supraregional liver unit in a teaching hospital. PATIENTS--1487 consecutive patients admitted during 1990 and 1991 (one year before and one year after introduction of the system). INTERVENTION--Introduction of a computerised protocol management system on 1 January 1991. MAIN MEASURES--The number and cost of clinical chemistry tests requested per patient day. RESULTS--The total number of clinical chemistry tests requested per patient day by the unit declined 17% (p < 0.001, Student's t test) and of out of hours tests requested per patient day from 0.31 to 0.16, 48% (p < 0.001; Mann-Whitney U test), resulting in a 28% reduction (p < 0.001) in direct laboratory expenditure per patient-day. Overall, the number of tests per admission decreased by 24% (p < 0.001; Mann-Whitney U test). CONCLUSION--Use of the computerised protocol management system resulted in closer compliance with the protocols and a significant reduction in the overall level of requesting. IMPLICATIONS--Although similar systems need to be tested in other clinical settings, computerised protocol management systems may be important in providing appropriate and cost effective health care.